GAMBARAN PROGRAM PENGEMBANGAN KAWASAN TANPA ASAP ROKOK DI DESA SUMBER HARUM KECAMATAN MAPPEDECENG KABUPATEN LUWU UTARA - Kasim Kasim; Abdul Muhaimin Taiyeb (-, 2022)
ABSTRACT  Background: Indonesia is the 5th largest country in the world that produces tobacco. In terms of the number of smokers, Indonesia is the 3rd largest country in the world after China and India. The prevalence of smoking among adults (10 years and over) in 2007 was 29.2%. The Global Youth Tembacco Survey (GYTS) Indonesia in 2006 reported that more than 37.3% of students (aged 13-15 years) had smoking habits. Cigarette smoke is very harmful to health. smokers and around other people. Although there is no data that explains that the disease is caused entirely by cigarette smoke. The total morbidity rate of blood vessel disease (hypertension) in 2020 is 2039 people or 99/1000 population and the death rate due to disease (hypertension and stroke). Objective: to provide an overview and information of the commitment development program for a smoke-free area in the working area of the UPTD Puskesmas Cenadana Putih, North Luwu Regency so that it can be useful for all plants, both from government agencies, professional organizations, NGOs, social organizations and the community. The survey method is a method of collecting data that is carried out on large and small populations, but the data studied are data taken from PHBS for the last 3 years in Sumber Fragrant Village, Kec. Mappedeceng. Research Results: Based on the indicators of success, the development of smoke-free areas has increased. From the results of PHBS data collection in September 2020, the coverage of smoking behavior indicators is 50.2% and the results of the KTR POKJA activity report in December 2020 the percentage of households that are smoke-free is .64.8%. After the stipulation of the Sumber Fragrant Village Regulation as a smoke-free area in public places such as: village offices, schools, poskesdes, posyandu and houses of worship, the table above describes 100% smoke-free. What is meant by social activities is religious activities carried out in the village of fragrant sources such as: recitation, yasinan and tahlilan. Conclusion: a smoke-free area is a solution to protect the whole community from exposure to other people'scigarette smoke.Keywords:, Program, Smoke No area, Society. ABSTRAK  Latar Belakang: Indonesia merupakan Negara Terbesar ke -5 di dunia yang memproduksi tembakau. Dari segi jumlah perokok, Indonesia merupakan negara terbesar ke-3 di dunia setelah Cina dan India. Prevalensi merokok dikalangan orang dewasa (10 Tahun ke atas ) Pada Tahun 2007 sebesar 29,2%. Global Youht Tembacco Survey (GYTS) Indonesia Tahun 2006 melaporkan lebih dari 37.3% pelajar ( usia 13-15 tahun) Mempunyai Kebiasan Merokok. Asap rokok sangat membahayakan kesehatan. siperokok maupun orang lain yang ada disekitarnya. Meskipun tidak ada data yang menerangkan bahwa penyakit tersebut disebabkan sepenuhnya oleh asap rokok. Total angka kesakitan Penyakit pembuluh darah (Hipertensi)Tahun 2020 sebesar 2039 orang atau 99 /1000 penduduk Dan angka kematian akibat penyakit (Hipertensi dan Stoke). Tujuan: untuk memberikan gambaran dan informasi Program   pembangunan komitmen kawasan bebas asap rokokdi wilaya kerja UPTD Puskesmas Cenadana Putih Kabupaten Luwu Utara sehingga dapat bermanfaat bagi semua tatanan  baik dari instansi pemerintahan, organisasi profesi, LSM, organisasi sosial kemasyrakatan dan  masyarakat. Metode: Metode survey merupakan sebuah metode pengumpulan data yang dilakukan pada populasi besar maupun kecil, tetapi  data yang dipelajari adalah  data yang di ambil dari PHBS 3 tahun terakhir di desa sumber harum kec. Mappedeceng. Hasil Penelitian: Berdasarkan indikator keberhasilan Program pengembangan kawasan bebas asap rokok mengalami peningkatan. Dari hasil pendataan PHBS pada september 2020 cakupan indikator prilaku merokok adalah 50,2% dan hasil  laporan  kegiatan POKJA KTR  pada bulan desember 2020 persentase rumah tangga yang bebas asap rokok adalah ,64,8%. Setelah ditetapkannya peraturan desa sumber harum sebagai kawasan bebas asap rokok di tempat-tempat umum seperti: kantor desa, sekolah, poskesdes, posyandu dan rumah ibadah dari tabel diatas menggambarkan 100% bebas asap rokok. Yang dimaksud kegiatan sosial kemasyarakatan adalah kegiatan keagamaan yang dilakukan didesa sumber harum seperti: pengajian, yasinan dan tahlilan. Kesimpulan: kawasan bebas asap rokok merupakan solusi untuk melidungi seluru masyarakat dari paparan asap rokok orang lain.Kata Kunci : Kawasan Tanpa Asap Rokok, Masyarakat, Program.